Preparation and Photocatalytic Properties of TiO2-Al2O3 Composite Loaded Catalysts - Jianzhong Pei; Weisi Ma; Rui Li; Yanwei Li; Hongzhao Du (Journal of Chemistry)
This paper presents an experimental approach to study catalytic effects of Fe3+ modified nanometer titanium dioxide (TiO2) loaded on aluminium oxide (Al2O3). Sol-gel method was used to prepare modified TiO2 loaded on carrier. Purification tests were conducted in a self-developed instrument to study catalytic effects of TiO2 loaded on Al2O3 with different contents through degradation rate. The modification mechanism was studied by scanning electron microscope (SEM). Results showed that loading on Al2O3 improved photocatalytic effect of TiO2 modified with Fe3+. The best photocatalytic effect was achieved under catalytic action of Al2O3 loaded with 10% TiO2 composite; the degradation rates were 6.9%, 13.8%, 21.4%, and 49.2%, respectively, 0.7%, 3.9%, 1.3%, and 15.1% larger than unloaded TiO2. SEM results of four catalysts showed that nanometer TiO2 was coated in form of grain on the surface of Al2O3. The optimal loading content was 10% at which the nanometer TiO2 grains were coated on the surface of Al2O3 uniformly.